Ethnic and Age Disparities in Outcomes among Liver Transplant Waitlist Candidates - Mustian, Margaux N. (Transplantation, 2019)
BACKGROUND: Despite the increasing prevalence of end-stage liver disease in older adults, there is no consensus to determine suitability for liver transplantation (LT) in the elderly. Disparities in LT access exist, with a disproportionately lower percentage of African Americans (AAs) receiving LT. Understanding waitlist outcomes in older adults, specifically AAs, will identify opportunities to improve LT access for this vulnerable population. METHODS: All adult, liver-only white and AA LT waitlist candidates (1/1/2003–10/1/2015) were identified in the Scientific Registry of Transplant Recipients. Age and race categories were defined: younger (age <60) white, younger AA, older white (age ≥60), and older AA. Outcomes were delisting, transplantation, and mortality and were modeled using Fine and Gray competing risks. RESULTS: Among 101,805 candidates, 58.4% underwent transplantation, 14.7% died while listed, and 21.4% were delisted. Among those delisted, 36.1% died, while 7.4% were subsequently relisted. Both older AAs and older whites were more likely than younger whites to be delisted and to die after delisting. Older whites had higher incidence of waitlist mortality than younger whites (sdHR 1.07; 95%CI:1.01–1.13). All AAs and older whites had decreased incidence of LT, compared with younger whites. CONCLUSIONS: Both older age and AA race were associated with decreased cumulative incidence of transplantation. Independent of race, older candidates had increased incidences of delisting and mortality following delisting than younger whites. Our findings support the need for interventions to ensure medical suitability for LT among older adults and to address disparities in LT access for AAs.